2016
DOI: 10.1016/j.neuroscience.2016.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Improved categorization of subtle facial expressions modulates Late Positive Potential

Abstract: Biases in facial expression recognition can be reduced successfully using feedback-based training tasks. Here we investigate with Event-Related Potentials (ERP) at which stages of stimulus processing emotion-related modulations are influenced by training. Categorization of subtle facial expressions (morphed from neutral to happy, sad or surprise) was trained with correct-response feedback on each trial. ERPs were recorded before and after training whilst participants categorized facial expressions without resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In order to manipulate task demand and avoid ceiling performance, emotions were morphed between neutral and emotional using the Morpheus Photomorphing Suite, creating ten intensity stages, labelled from 10% to 100%. Based on previous findings of improvements in expression recognition only at low intensities and a ceiling to performance increases beyond 50–60% ( Gao & Maurer , 2010 ; Pollux, Hall & Guo , 2014 ; Pollux , 2016 ) intensities of 70, 80 and 90% were removed whereas 100% was included to control for task comprehension, leaving a total of 84 images used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…In order to manipulate task demand and avoid ceiling performance, emotions were morphed between neutral and emotional using the Morpheus Photomorphing Suite, creating ten intensity stages, labelled from 10% to 100%. Based on previous findings of improvements in expression recognition only at low intensities and a ceiling to performance increases beyond 50–60% ( Gao & Maurer , 2010 ; Pollux, Hall & Guo , 2014 ; Pollux , 2016 ) intensities of 70, 80 and 90% were removed whereas 100% was included to control for task comprehension, leaving a total of 84 images used in the study.…”
Section: Methodsmentioning
confidence: 99%
“…This line of research reported early ERPs, such as N1, N2 and P2 (Tanaka et al , 1999; Antal et al , 2000; Antal et al , 2001; Xiao et al , 2015). Other categorization tasks, such as the valence categorization of emotional pictures, facial feature categorization, object-animal categorization and implicit association tests based on stimuli categorization, have elicited P3 (Delaney-Busch et al , 2016; Schupp et al , 2014; Fleischhauer et al , 2014; Chen et al , 2006) or late positive potential (LPP) (Delaney-Busch et al , 2016; Schupp et al , 2014; Chen et al , 2006; DaSilva et al , 2016; Pollux, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…We also observed that herding choices elicited a larger LPP amplitude than anticonformity choices. A considerable number of studies have found that LPP component may reflect the neurophysiological mechanism of categorical processing (Chen et al, 2006; Schupp et al, 2014; daSilva et al, 2016; Delaney-Busch et al, 2016; Pollux, 2016), and the stimuli leading to better evaluation categorization will elicit an increased LPP amplitude (Chen et al, 2010; Wang et al, 2016; Jin et al, 2017). As people tend to believe what most others believe (Deutsch and Gerard, 1955; Chen et al, 2010; Shen et al, 2018), participants in this study were likely to evaluate an industrial zone with a high occupancy rate better and classify it as a categorization of better evaluation (compared with an industrial zone with a low occupancy rate), which was mirrored by a larger LPP amplitude.…”
Section: Discussionmentioning
confidence: 99%